Model‐free distributed optimal control for continuous‐time linear systems. Issue 16 (20th August 2022) - Feng, Xinjun; Zhao, Zhiyun
Abstract: This paper studies the distributed optimal consensus problem for a group of continuous‐time linear systems in the scenario that the dynamics of linear systems are completely unknown. Both an optimal state feedback control law and an optimal output feedback control law are constructed by solving the Algebraic Riccati Equation (ARE) that contains no global information, which guarantees the consensus of linear systems and the global optimality. Adaptive Dynamic Programming (ADP) method is presented to solve the ARE, thus the control algorithms are not relying on the dynamics of linear systems any more. Finally, numerical simulation results are presented to demonstrate the efficiency of proposed approach.